Propriedades químicas e biológicas do solo enriquecido com biocarvão e cultivado com cana-de-açúcar - César Florentino Puma Vega (2024)
Researches carried out in recent years on the potential of biochar as a conditioner of soil properties has shown in general favorable results for plant cultivation. However, little is known about its long-term effects and/or when applied in the form of granulated organomineral fertilizer for seedling production. The objectives of this study were 1) to evaluate the effects of biochar on the chemical and biological properties of the soil and on sugarcane productivity over five years; 2) evaluate soil properties, growth and nutrition of pre-sprouted sugarcane seedlings fertilized with granulated organomineral fertilizers, produced from biochar. They were carried out three experiments. Experiment I was carried out in the field, in a randomized block design in a factorial scheme 4x2+2 additional treatments (Control 1 and 2), and four replications. The factors corresponded to the biochar doses (10, 20, 30 and 40 Mg ha-1) and their combinations without and with NPK mineral fertilizer. Control 1 corresponded to natural soil, without biochar and without NPK fertilizer, and Control 2 to soil with application of NPK fertilizer. Experiments II and III were conducted over a period of 60 days, in a greenhouse and in a completely randomized design. In experiment II, the soil with different organomineral fertilizers (treatments) was incubated in pots with a capacity of 0.5 dm3. The treatments were: Control – no fertilizer (T); biochar (B); mineral fertilizer with NPK (M); biochar with NPK mineral fertilizer (BM); organomineral fertilizer, produced from biochar and NPK mineral fertilizer (OM). In experiment III, conducted in the same way as experiment II, pre-sprouted sugarcane seedlings were produced. In experiment I were evaluated sugarcane productivity, chemical, physical and biological activity of the soil and activity of growth-promoting bacteria. Maximum sugarcane productivities occur with the application of 37.71 Mg ha-1 and 31.00 Mg ha-1 of biochar, in treatments without and with application of NPK fertilizer, respectively. The doses of biochar favored the chemical and biological properties of the soil, except for diazotrophic bacteria where there was no effect. In experiments II and III, the release of nutrients from NPK mineral fertilizer, alone or in mixture with biochar was rapid, while that from organomineral fertilizer was relatively slow. The highest accumulations of nutrients in the aerial part of sugarcane plants were in treatments with NPK mineral fertilizer, alone or in mixture with biochar, followed by organomineral fertilizer, control and biochar, in that order.